In search of a new quality of urban living. A contemporary vision of the garden-city and its derivatives: new challenges and solutions for self-containment in urban areas - Kleszcz, Justyna (Bulletin of Geography. Socio-economic Series, 2025)
The article discusses research on the ideal place of residence for modern individuals, based on theoretical concepts and urban housing estates designed with self-containment and Howard’s 1898 garden city concept in mind. The paper presents a comparative analysis of theoretical designs and contemporary implementations related to urban agriculture principles influenced by Howard’s concept. A typology of theoretical solutions is developed and compared to built facilities, revealing differences and reasons for their creation.